Whistleblower Rights and Protection in The Workplace: the Role of Trade Unions in Poland Selected Issues - Kobroń-Gąsiorowska, Łucja (Acta Universitatis Lodziensis. Folia Iuridica, 2021)
The article discusses selected problems related to trade unions’ functions and their future role in the protection of whistleblowers. The author analyzes the current provisions of the Act on Trade Unions concerning the functioning of trade unions in protecting whistleblowers in the workplace, reporting irregularities (illegal, unethical or otherwise inappropriate activities) and the use of collective bargaining power of trade unions. Workers’ representatives have an express right to assist whistleblowers as defined by national law. The author states that the functions of trade unions under trade union law in Poland in reporting irregularities are often perceived as signaling and, consequently, limited.